2019
DOI: 10.3390/su11123358
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences of Sustainability Labeled Cut Roses in Germany

Abstract: The study investigated preferences of consumers of food retailing outlets in Germany for sustainability labeled cut roses. A sample of 1201 respondents of an online survey was used to analyze their preferences based on a choice-based conjoint experiment in which a bunch of 10 roses was considered which differed concerning the labeling certificate, country of production of the plants, price, packaging, smell, and blossom size of the roses. Latent class analysis revealed existence of consumer heterogeneity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Growers and sellers may perceive these changes as the development of new, innovative products for the markets. Based on the results of recent surveys, consumers were willing to pay more (≈15% more) for sustainable floricultural products, although clear and precise labeling was necessary for discrimination [74][75][76]. Evaluating the sustainability and the quality criteria for German consumers, it was indicated that both cut rose quality parameters such as blossom uniformity and flower scent were as important as sustainable practices (e.g., choice of packaging) [76].…”
Section: Sustainability Perception Of Growers Sellers and Consumersmentioning
confidence: 99%
“…Growers and sellers may perceive these changes as the development of new, innovative products for the markets. Based on the results of recent surveys, consumers were willing to pay more (≈15% more) for sustainable floricultural products, although clear and precise labeling was necessary for discrimination [74][75][76]. Evaluating the sustainability and the quality criteria for German consumers, it was indicated that both cut rose quality parameters such as blossom uniformity and flower scent were as important as sustainable practices (e.g., choice of packaging) [76].…”
Section: Sustainability Perception Of Growers Sellers and Consumersmentioning
confidence: 99%
“…With the absence of flower fondness as a driver, perhaps German men rely on their understanding or familiarity with cut flowers as a gift, especially when compared to other gift items. Cut flowers are a safe, traditional, and appropriate gift in German culture [21]. Alternative gifts such as candles, books, gift certificates, and photo frames, may be less understood or may not have the same versatility and could potentially lead to unintended or confusing messages for the receiver.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, consumers like to buy floral gifts from a local flower retailer [18], because they appreciate the florist's advice, social interaction, and the sensory stimulation in the flower shop [19,20]. Others buy in supermarkets or discounters, often due to budget and time constraints [21]. Regardless of whether consumers buy from specialized or general retailers, the sensory contact with cut flowers is important to them.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the segment of ethically conscious consumers buying fair tradecertified horticultural food and non-food items such as coffee, bananas, chocolates and cut flowers has steadily increased in Germany [1][2][3][4][5][6][7][8]. This can be attributed to heightened consumer awareness, understanding of sustainable production and issues of environmental and social sustainability [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the segment of ethically conscious consumers buying fair tradecertified horticultural food and non-food items such as coffee, bananas, chocolates and cut flowers has steadily increased in Germany [1][2][3][4][5][6][7][8]. This can be attributed to heightened consumer awareness, understanding of sustainable production and issues of environmental and social sustainability [6,9]. Given that the concept of fair trade is closely aligned with various United Nations Sustainable Development Goals (SDGs), including poverty alleviation (goal 1), gender equality (goal 5), decent work and economic growth (goal 8), responsible consumption and production (goal 12) and climate actions, many ethical conscious consumers are in favor of fair trade certified products [10,11].…”
Section: Introductionmentioning
confidence: 99%